Percepção da imagem corporal e fatores associados em idosos - SILVA, Jacqueline Aparecida Assis (2020)
The concept of body image is defined as a multidimensional construct, which involves how the individual acts, feels, imagines and sees his appearance and his own body. Dissatisfaction with self-image in the elderly can be harmful to health, and the idealization of a body pattern can induce harmful behavior. The aim of the study was to analyze the association of body image perception with sociodemographic, health and behavioral aspects. The cross-sectional study was developed from data extraction from the ELSIA Project - Longitudinal Study of Health of the Elderly of Alcobaça, BA, which evaluated 460 elderly people. The elderly participants had their anthropometric measurements measured, and also answered, in the form of an individual interview, a multidimensional questionnaire to assess the perception of body image and the sociodemographic, health and behavioral aspects. Stunkard's scale of silhouettes was used to assess the dependent variable. The prevalence of dissatisfied elderly people was 63.5%, of these 64.7% were dissatisfied with being overweight and 35.3% with thinness. Dissatisfied elderly people had a higher mean weight of 69.43 kg ± 15.03 (p <0.001) and BMI 28.09 kg / m² ± 5.73 (p = 0.001). A significant association was found between body image and the variables number of diseases (p <0.001), number of medications (p = 0.018), functional disability in IADL (p = 0.010) and BMI (p <0.001). In the analysis of the prevalence ratio, in the bivariate analysis it was associated with the perception of body image with the sociodemographic aspects (years of study and family income), health aspects (number of diseases and number of medications) and behavioral aspects (IADL, BMI and activity physics). However, after the adjusted analysis, health (number of diseases) and behavioral aspects (AIVD and BMI) remained associated with the perception of body image. The results of the present study highlight the high prevalence of body image dissatisfaction, being essential interventionist health promotion strategies that enable the elderly to better body selfknowledge, avoiding adoptions of behaviors harmful to health and quality of life.